1996
DOI: 10.1128/jb.178.10.2883-2889.1996
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms of Escherichia coli succinyl-coenzyme A synthetase regulation

Abstract: Low concentrations of ADP are shown to increase the rate of phosphoenzyme formation of E. coli succinylcoenzyme A (CoA) synthetase (SCS) without altering the fraction of phosphorylated enzyme. This is true when either ATP or succinyl-CoA and P i are used to phosphorylate the enzyme. The stimulatory effect of ADP is not altered by sample dilution, is retained upon partial purification of the enzyme, and reflects the binding of ADP to a site other than the catalytic site. GDP also alters the phosphorylation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Although much interest was devoted to the structure (6,11,12), function, regulation (13), and nucleotide specificity (14,15), only little is known about the substrate range concerning carbon acids. Among the more than 30 members of the subsubclass acid CoA ligases (EC 6.2.1), miscellaneous descriptions about extended ranges concerning the acid substrates for the enzymes have been published.…”
mentioning
confidence: 99%
“…Although much interest was devoted to the structure (6,11,12), function, regulation (13), and nucleotide specificity (14,15), only little is known about the substrate range concerning carbon acids. Among the more than 30 members of the subsubclass acid CoA ligases (EC 6.2.1), miscellaneous descriptions about extended ranges concerning the acid substrates for the enzymes have been published.…”
mentioning
confidence: 99%
“…The reaction is completely reversible and supplies also succinyl-CoA for heme biosynthesis and ketone body activation, in particular during anaerobic growth (32). Several studies elucidating a variety of regulation systems, indicated the importance of SucCD as a control point of the citric acid cycle (5). Succinyl-CoA synthetases consist of ␣ (SucD) and ␤ (SucC) subunits, with mass ranges of 29 to 34 kDa and 41 to 45 kDa, respectively (49).…”
mentioning
confidence: 99%
“…However, the deletion of these genes did not significantly improve adipic acid production. As succinyl-CoA is an important cofactor in the formation of β-ketoadipyl-CoA, sucCD ( sucC and sucD , which encode subunits of succinyl-CoA synthetase) were deleted to minimize the competing conversion of succinyl-CoA towards succinate ( Birney et al, 1996 ; Zhao et al, 2018 ). β-Ketoadipyl-CoA thiolase ( paaJ ) is also targeted for deletion due to its role in the reversible catalysis of β-ketoadipyl-CoA to succinyl-CoA and acetyl-CoA ( Yu et al, 2014 ; Babu et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%